A multi-statistical approach for estimating the total output of CO2 from diffuse soil degassing by the accumulation chamber method. (April 2016) - Elío, J.; Ortega, M.F.; Nisi, B.; Mazadiego, L.F.; Vaselli, O.; Caballero, J.; Chacón, E.
Highlights: The total CO2 output has high relevance for quantifying a leakage. The CO2 output was estimated after measuring the flux with an accumulation chamber. A methodology for estimating the total output of CO2 was proposed. Eight campaigns were carried out at Hontomín site and in four natural CO2 seepages. Six different statistical methods to estimate the total CO2 output were evaluated. Abstract: CO2 flux measurements at the soil–atmosphere interface are commonly carried out as part of site characterization in areas elected for CO2 geological storage purposes. This approach represents an important monitoring tool to detect and quantify leakages during operational and post-operational stages related to the injection of anthropogenic CO2 . A large variety of techniques to measure diffuse CO2 soil flux is available and one of the most widely used is the accumulation chamber method. With this method, the total output is statistically estimated after measuring the CO2 flux in selected points of a certain area. Several statistical approaches can be applied and it is important to select the most representative and significant procedure. Consequently, in this paper six different methods were used to calculate the total CO2 output, as follows: arithmetic mean, minimum variances unbiased estimator, bootstrap resample, partitioning of data into different populations with graphical and maximum likelihood procedures, and sequential Gaussian simulation. Eight campaigns were carried out in the Hontomín CO2 Storage Technology Development Plant (Burgos, Spain) and in natural analogs of CO2 storage (Campo de Calatrava, Spain and Mt. Amiata, Caprese Michelangelo and La Solfatara, Italy). Our results showed that sequential Gaussian simulation is the most precise method for evaluating the total CO2 output and the respective confidence interval. Nevertheless, the estimation of the total CO2 output with other statistical methodologies allowed to develop an application procedure for choosing the most reliable and realistic approach.